Factors affecting the water odor caused by chloramines during drinking water disinfection - Wang, An-Qi; Lin, Yi-Li; Xu, Bin; Hu, Chen-Yan; Gao, Ze-Chen; Liu, Zhi; Cao, Tong-Cheng; Gao, Nai-Yun (The Science of the total environment, 2018)
Chloramine disinfection is one of the most common disinfection methods in drinking water treatment. In this study, the temporal variability of water odors during monochloramine auto-decomposition was investigated to elucidate the characteristics of odor problems caused by adopting chloramine disinfection in tap water. Odor intensities and dominant odorant contributions were determined using the flavor profile analysis (FPA) and odor active value (OAV), respectively. During auto-decomposition of monochloramine, Cl2/N molar ratio, pH, temperature, and the presence of NOM all affected odor intensity and odor temporal variation in drinking water. In general, decreasing pH from 8.5 to 6.0 led to increasing perceived odor intensity due to the formation of dichloramine. The major odorants responsible for chlorinous odor under acidic and non-acidic conditions were dichloramine and monochloramine, respectively. Chloraminated water with a Cl2/N molar ratio of 0.6 or NOM concentration <2 mg-C L−1 inhibited odor intensity. Furthermore, the influence of rechlorination on chlorinous odor intensity for chloraminated water should not be neglected. The results of this study will be beneficial for the control of chlorinous odors caused by chloramine disinfection in drinking water. [Display omitted] •Dichloramine played a significant role in chloraminated water odors under acidic conditions.•Lower Cl2/N molar ratio was generally better for water odor control.•Temperature and retention time in distribution system affect water odor.•Odorous organic chloramines contributed to water odors in the presence of NOM.